Safety and Observations in a Pilot Study of Lenalidomide for Treatment in Autism. (11th September 2012) - Chez, Michael; Low, Renee; Parise, Carol; Donnel, Tammy
Abstract : Autism affects 1 : 88 children in the United States. Familial history of autoimmune disease, autoantibodies in the serum of mothers when there is more than one autistic offspring, and neuroglial response in CSF and brain tissue in autistic patients suggest an immunological variable may be associated with this condition. Lenalidomide has the potential to invoke changes in TNF- α with less toxicity than thalidomide. This pilot study evaluated lenalidomide at reduction of TNF- α and improvement of behavior and language in children with autism with elevated TNF- α . Subjects with elevated TNF- α were given 2.5 mgs lenalidomide daily for 12-weeks. Pharmacodynamics and safety was evaluated. Changes in language and autistic behaviors after six and twelve weeks were measured. Although statistical significance was not achieved for most measures, there were trends toward improvement. After 6-weeks, mean receptive language increased: 60.67 ± 12.06 to 65.00 ± 15.10 ( P = 0.11) and symptoms of autism decreased (40.75 ± 5.96 versus 38.67 ± 7.90, P = 0.068). After 12-weeks, CSF-TNF- α declined 57% ± 25% from 80.5 ± 41.03 to 38.0 ± 31.27 ( P = 0.068). Serum TNF- α declined 57% (92.50 ± 68.92 to 40.25 ± 44.53 ( P = 0.048). This study suggests that lenalidomide is tolerated as a treatment by children with autism and should be further studied as a potential agent for cytockine inflammation.